Visual health burden among industrial workers in Noida, India: an epidemiological study - Tiwari, Priyanshu; Jain, Ishika; Sah, Ruchika; Sah, Manish Kumar (International Journal Of Community Medicine And Public Health, 2025)
Background: To assess the prevalence, risk factors, and impact of visual health issues among industrial workers in Noida, India, Methods: This study employed a cross-sectional design to assess the ocular health burden among industrial workers in Noida, India. Data collection included structured questionnaires, vision screening tests, and comprehensive ocular examinations conducted by trained optometrist. The questionnaires gathered information on demographics, occupational exposure, visual symptoms, and eye care practices. Vision screening included tests for visual acuity, refractive errors, slit-lamp assessments, and fundus examination. Results: A total of 638 industrial workers attended the eye camp, with 279 (43.73%) having normal vision and 359 (56.26%) experiencing eye problem. Refractive error (25.91%) was the most common ocular issue, followed by presbyopia (12.81%) and cataract (8.64%). The construction industry had the highest prevalence (31.48%), followed by rubber/plastic (12.81%) and textiles (12.26%). Conclusions: The study indicates a high prevalence of ocular morbidity, likely influenced by workplace hazards such as dust, chemical exposure, poor lighting, and prolonged screen use. Addressing these concerns through regular vision screenings, workplace safety measures, and awareness programs is crucial.